2008
DOI: 10.1620/tjem.214.191
|View full text |Cite
|
Sign up to set email alerts
|

The EFA6 Family: Guanine Nucleotide Exchange Factors for ADP Ribosylation Factor 6 at Neuronal Synapses

Abstract: ADP ribosylation factor 6 (ARF6) is a member of the ARF family of small GTPases, which mediates a variety of neuronal functions accompanying the structural changes of developing and mature neurons through its regulation of actin cytoskeleton reorganization and membrane traffi c. The activation of ARF6 is strictly regulated by guanine nucleotide exchange factors (GEFs). The EFA6 family is the fi rst member that was identifi ed to be a specifi c GEF for ARF6 and comprises four structurally related polypeptides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…All ARF6 GEFs possess a pleckstrin homology domain that serves as a binding site for specific phosphoinositides and/or partner proteins. They are recruited to the membranes through an interaction with PIP 2 or PIP 3 , depending on the different affinities of pleckstrin homology domains for these phospholipids (83,84). The synthesis of PIP 2 and/or PIP 3 may be one of the major mechanisms through which ARF6 is activated at the membrane in response to agonist stimulation of cells (85).…”
Section: Discussionmentioning
confidence: 99%
“…All ARF6 GEFs possess a pleckstrin homology domain that serves as a binding site for specific phosphoinositides and/or partner proteins. They are recruited to the membranes through an interaction with PIP 2 or PIP 3 , depending on the different affinities of pleckstrin homology domains for these phospholipids (83,84). The synthesis of PIP 2 and/or PIP 3 may be one of the major mechanisms through which ARF6 is activated at the membrane in response to agonist stimulation of cells (85).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that ARF6 activation is precisely regulated by ARF6 GEFs in a spatiotemporal manner, leading to neuronal development and synapse formation (7,50). Cytohesin1 and -2, EFA6A-D, and brefeldin A-resistant ARF-GEF1-3 are well known positive regulators for ARF6 activation (51).…”
Section: Arf6-mediated Spine Formation Ismentioning
confidence: 99%
“…This suggests that ACAP1 promotes integrin-dependent outgrowth, functioning through its ARF6 GAP activity and not by its function as a coat protein. We next investigated the effects of activating ARF6 using two ARF6 GEFs that are expressed in neurons, EFA6 (Sakagami, 2008) and ARNO (Hernández-Deviez et al, 2002Hernández-Deviez and Wilson, 2005). EFA6 has ARF6-specific GEF activity (Franco et al, 1999;Macia et al, 2001), while ARNO is reported to have some ARF1 GEF activity in vitro, but is considered to be principally an ARF6 GEF (Frank et al, 1998;Venkateswarlu and Cullen, 2000;Macia et al, 2001;Gillingham and Munro, 2007;Hofmann et al, 2007).…”
Section: Are Integrins Rapidly Transported Over Long Distances Via Armentioning
confidence: 99%